Should we recommend low-fat diets for obesity? - Pirozzo, S; Summerbell, C; Cameron, C; Glasziou, P (2003)
Dietary fat intake has been blamed for the increase in adiposity and has led to a worldwide effort to decrease the amount of fat in the diet. However, the comparative efficacy of this approach is debatable. Whilst short-term dietary intervention studies show that low-fat diets lead to weight loss in both healthy and overweight individuals, it is less clear if a reduction in fat intake is more efficacious than other dietary restrictions in the long term. The purpose of this systematic review was to determine the effectiveness of low-fat diets in achieving sustained weight loss when used for the express purpose of weight loss in obese or overweight people. A comprehensive search identified six studies that fulfilled our criteria for inclusion (randomized controlled trial, participants either overweight or obese, comparison of a low-fat diet with another type of weight-reducing diet, follow-up period that was at least 6 months in duration and inclusion of participants 18 years or older without serious disease). There were a total of 594 participants in the six trials. The duration of the intervention varied from 3 to 18 months with follow-up from 6 to 18 months. There were no significant differences between low-fat diets and other weight-reducing diets in terms of sustained weight loss. Furthermore, the overall weight loss at the 12-18-month follow-up in all studies was very small (2-4 kg). In overweight or obese individuals who are dieting for the purpose of weight reduction, low-fat diets are as efficacious as other weight-reducing diets for achieving sustained weight loss, but not more so.